Биоэтический тренд синтетической биологии - Буряк, В.В. (Культура народов Причерноморья, 2014)
Синтетическая биология является одним из наиболее значимых интеллектуальных и технонаучных проектов в контексте эвоюции развёртывания ноосферы. В настоящее время в глобальном сообществе большое внимание уделяется не только различным отраслям науки, но и наукоемким технологиям, энергетике, биомедицине, экологии. В связи с этой тенденци методология научных исследований обретает специфические особенности в контексте становления вузовских дисциплин. Систематизированы наиболее значимые направления современных междисциплинарных методологических подходов. Синтетична біологія є одним з найбільш значущих інтелектуальних проектів в контексті перспектив розгортання ноосфери. В даний час в суспільстві велика увага приділяється не тільки різним галузям науки, але і наукомістких технологій, енергетиці, біомедицині, екології. У зв'язку з цим методологія наукових досліджень має специфічні особливості в контексті вузівських дисциплін. Біотехнології розглядаються в плані інтеграції філософії та методології науки з іншими сферами науки і цінностями постіндустріального суспільства. Інтерпретується образ сучасної науки, а також розглядаються основні проблеми, що виникають в ході біоетичних досліджень. Систематизовані найбільш значущі напрями сучасних міждисциплінарних методологічних підходів. Complex contradictions of modern civilization are a serious challenge for each individual, social groups and states. The theme of the radical transformation of the body and the human psyche has been the subject of sharp philosophical and bioethical debates. Today it is obvious that the most dynamic factor in the transformation of the economy, society, politics and culture were high-tech. The most rapid cluster development - emergent technologies, significant object of research, philosophers, social theorists, cultural anthropologist. Synthetic biology is one of the most significant intellectual and technological projects in the context of the deployment noosphere. At the moment in the global community a lot of attention is paid not only to the various branches of science, but also high-end technologies, energy, biomedicine and ecology. In response to this trend research methodology acquires specific features in the context of the emergence of university disciplines. Diversified biotechnology is discussed in terms of integration of philosophical knowledge and other areas of science. Context of the implementation of projects is transdisiplinary reassessment of values of postindustrial society. Image of modern science emerged in the era of modernism and is based on the priority of promoting expertise, methodological private diversification strategies. History and methodology of science - the most important sphere of modern university education, which formed effective cognitive approaches to understanding the social and cultural situation of cash. The paper discusses the main problems arising in the course of crossdisciplinary discussions, in particular - multi bioethical research. Systematized the most important areas of modern interdisciplinary methodological approaches.